DC-DC Buck and Boost Converter Design for Energy Control in Hybrid PV Systems - Zaini Zaini; Wisnu Joko Wulung (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2023)
The intermittent nature of photovoltaic (PV) power generation due to weather conditions and time of day can affect the ability of PV systems to satisfy load demand. An effective PV system must store excess electrical energy when generation exceeds demand and discharge stored energy when demand is greater than generation. This study utilizes MATLAB simulations to design and evaluate DC-DC converter circuits for battery charging and discharging in PV systems. For charging, a buck converter with a fixed 45 V source is able to reduce voltage to a range of 33.99 V to 1.46 V by decreasing the duty cycle. For discharging, a boost converter with a fixed 12.8V source can increase voltage to 16.90 V–33.49 V by raising the duty cycle. Furthermore, under equal comparison, the open-loop buck converter operating at a 35% duty cycle demonstrates worse overshoot of 14.36% versus 0.24% for the closed-loop PID controlled buck converter. Similarly, the open-loop boost converter at 70% duty cycle exhibits slightly higher overshoot of 0.47% compared to negligible overshoot for the closed-loop PID controlled boost converter.